Semiotika Roland Barthes: Analisis Foto Ibu Sumarsi Di Aksi Kamisan - Marsila, Firda Raudhah; Ummah, Syadathul (Tanra: Jurnal Desain Komunikasi Visual Fakultas Seni Dan Desain Universitas Negeri Makassar, 2025)
This article discusses the study of semiotics in the protest photos of Mrs. Sumarsih at the kamisan action. This research will discuss an in-depth analysis of the photo of Mrs. Sumarsih as one of the people who often voiced the rights of of human rights violations by using Roland Barthes semiotic analysis. The implications of this research were obtained from primary data that obtained from in-depth analyzing the photo showing Mrs. Sumarsih brandishing a red card in front of the Merdeka Palace and secondary data sources that were obtained through literature sources such as books, journals, theses, and the internet.